ANALISIS PENYEDIAAN LOKASI LAHAN TERBANGUN (PERMUKIMAN) BAGI MASYARAKAT YANG TERKENA TSUNAMI DI KABUPATEN DONGGALA KECAMATAN BANAWA - Dewa P. Christabel J.; Esly D. Takumansang; Amanda S. Sembel (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
Housing and settlements are one of the basic human needs. Settlement is part of a residential environment consisting of more than one housing unit that has infrastructure, facilities, public utilities, and has supporting activities for other functions in urban areas or rural areas. The government is obliged to meet the housing needs of the Indonesian people.The earthquake and tsunami disaster in Donggala Regency, Banawa District has caused damage to community housing. As a result of this disaster, it is necessary to provide new residential land locations for disaster-affected communities in Banawa District. This study aims to provide an understanding in analyzing the suitability of residential land in Donggala Regency, Banawa District and to assist the government in determining a suitable location for a new residential area in Donggala Regency, Banawa District. To determine the right location in building regional residential areas, the unit analysis method of land capability and land suitability is used. The results of the research show that the land capability in Donggala Regency is still in the category that can be developed but still has to follow the appropriate directions and rules for the development category. Meanwhile, land suitability in Donggala Regency, the Agricultural area has the most dominating area. The right land location for the development of the new settlement area is located in Banawa District, Gunung Bale Village.